The fall of AAP government - Farooqui, Jamil (Radiance Views Weekly, 2014)
The fall of the AAP government in Delhi is a bolt out of the blue for Indian electorate in general and for common people in particular. It has shattered their dreams and demolished all their hopes for betterment. The people of Delhi voted AAP to power as it associated itself with the problems, desideratum and aspirations of the so-called common people and promised to ease the burdens of day-to-day life. The party took measures to fulfil some of the promises it had made to the electorate and initiated some drastic steps for others. People were happy with their decision to bring the party into power and pinned more hopes and aspirations to it. However, all of a sudden the chief architect of the party, Arvind Kejriwal decided to enact ‘Janlokpal Bill’ and put it at the floor of the house, without following the required procedure, knowing that the party had no sufficient strength to pass the bill and its supporter was against it. Obviously, the bill was rejected due to the lack of required votes, and the Chief Minister had to resign. This episode shocked the people and led them to draw different impressions of the situation.